Socialization of Community Needs-Based Financial Management in Pakning Asal Village - Jesika Puteri; Novilasari Novilasari; Tiara Lestari (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Village financial management is a strategic instrument in supporting development and improving community welfare. However, in practice, village financial management is often not fully based on the actual needs of the community and lacks public participation in budgeting and oversight processes. This community service activity aims to enhance community understanding and participation in needs-based financial management in Pakning Asal Village. The activity employed a descriptive and participatory approach through socialization, interactive presentations, open discussions, and the dissemination of informational media. The participants included village officials, community leaders, and residents of Pakning Asal Village. The results indicate an improvement in participants' understanding of transparent, accountable, and community-oriented village financial management principles. Furthermore, the activity fostered collective awareness of the importance of active community involvement in planning, implementing, and evaluating the use of village funds. Overall, this community service program contributes to strengthening participatory village financial governance and supports the realization of more effective and sustainable village development.